Geometrically mediated droplet merging in microchannels - Niu,X; Edel,JB (2008)
We present a novel method for controllably merging aqueous microdroplets within segmented flow microfluidic devices. Such geometrically mediated droplet merging involves simple fabrication procedures and is extremely robust in operation. Passive droplet merging of this type is likely to find application, in multistep ana-lytical procedures at high-throughput.